Dietary supplementation with Cyberlindnera jadinii improved growth performance, serum biochemical Indices, antioxidant status, and intestinal health in growing raccoon dogs (Nyctereutes procyonoides) - Zhao, Dehui; Liu, Hanlu; Zhang, Haihua; Liu, Keyuan; Zhang, Xinyu; Liu, Qian; Wu, Yan; Zhang, Ting; Zhang, Qiaoru (Frontiers in Microbiology, 2022)
This study was conducted to investigate whether different dietary Cyberlindnera jadinii levels affect the growth performance, serum immunity, antioxidant capacity and intestinal microbiota of growing raccoon dogs. Forty-five healthy male raccoon dogs were randomly assigned to three treatment groups, with 15 raccoon dogs per group. Each raccoon dog was housed in an individual cage. The raccoon dogs in the three groups were fed diets supplemented with Cyberlindnera jadinii at dosages of 0 (N group), 1 x 109 (L group) and 5 x 109 CFU/g (H group). A 7-day pretest period preceded a formal test period of 30 days. The results show that the Cyberlindnera jadinii in L and H groups significantly improved the average daily gain (ADG) (P < 0.01) and decreased the ratio of feed to weight (F/G) (P < 0.05). The serum IgA, IgG, IL-2 and IFN-α were significantly higher in the L and H groups than those in the N group (P < 0.05), and the serum IL-6 level was significantly lower in the L group than that in the N and H groups (P < 0.05). Cyberlindnera jadinii supplementation significantly increased the serum SOD activities (P < 0.01), and the serum GSH-Px activity was significantly higher in the L group than that in the N and H groups (P < 0.05). Cyberlindnera jadinii addition increased Firmicutes, Actinobacteriota, Megasphaera and Bifidobacterium levels, while it decreased Bacteroidota, unidentified_Bacteria and Prevotella levels (P < 0.05). The relative abundance of Proteobacteria, Cyanobacteria and Dialister were significantly higher, the relative abundance of Blautia and Agathobacter in the H group than those in the N and L groups (P < 0.05). The ratio of Firmicutes to Bacteroidetes in the Cyberlindnera jadinii supplementation groups significantly increased compared with that in the N group. In conclusion, dietary supplementation with Cyberlindnera jadinii increased growth performance, serum immunity, antioxidant capacity, and improved intestinal microbiota in growing raccoon dogs. Cyberlindnera jadinii can be used as growth promoters of raccoon dogs.